THE ALIGNMENT AND MISALIGNMENT OF THE ISLAMIC ECONOMICS CURRICULUM WITH THE INDONESIAN GOVERNMENT POLICY - Sutan Emir Hidayat; Sudarmawan Samidi; Atiqoh Nasution (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2021)
The purpose of this paper is to explore the equivalency of curriculum content of universities. It examines how this equivalency can benefit the universities that offer Islamic economics programs in implementing the new policy of the Indonesian Education and Culture Minister, especially for point No. 4, known as